Respuesta :
Answer:
[tex]u(x)=\ =\ e^x(xcosy\ -\ ysiny)\ \textrm{is harmonic.}[/tex]
[tex]\textrm{conjugate function},\ v\ =\ 2e^x(xsiny\ +\ ycosy)\ +\ c[/tex]
Step-by-step explanation:
As given in question,
- [tex]u(x)\ =\ e^x(xcosy\ -\ ysiny)[/tex]
[tex]=\ e^x.xcosy\ -\ e^x.ysiny[/tex]
[tex]=>\ u'_x(x)\ =\ e^x.cosy\ +\ xe^xcosy\ -\ ye^xsiny\\\\=>\ u''_x(x)\ =\ e^xcosy+e^xcosy+xe^xcosy-e^xysiny\\\\=>\ u'_y(x)\ =\ -e^x.xsiny\ -\ e^xsiny\ -\ e^x.ycosy\\\\=>\ u''_y(x)\ =\ -xe^xcosy\ -\ 2e^xcosy\ +\ e^x.ysiny[/tex]
For a system to be harmonic,
[tex]\dfrac{\partial^2 u}{\partial x^2}\ +\ \dfrac{\partial^2 u}{\partial y^2}\ =\ 0[/tex]
From the above calculated value we can see that
[tex]\dfrac{\partial^2 u}{\partial x^2}\ +\ \dfrac{\partial^2 u}{\partial y^2}[/tex]
[tex]=\ e^xcosy+e^xcosy+xe^xcosy-e^xysiny\ -\ xe^xcosy\ -\ 2e^xcosy\ +\ e^x.ysiny[/tex]
= 0
So, given function u(x) is harmonic.
Now to find conjugate function of u,
[tex]dv\ =\ \dfrac{\partial v}{\partial x}.dx\ +\ \dfrac{\partial v}{\partial y}.dy[/tex]
According to Cauchy-Riemen Equation,
[tex]\dfrac{\partial u}{\partial x}\ =\ \dfrac{\partial v}{\partial y}\\\\\dfrac{\partial u}{\partial y}\ =\ -\dfrac{\partial v}{\partial x}[/tex]
So, we4 can write the above equation as,
[tex]dv\ =\ -\dfrac{\partial u}{\partial y}dx\ +\ \dfrac{\partial u}{\partial x}dy[/tex]
on putting the values, we have
[tex]dv\ =\ -(-e^x.xsiny\ -\ e^xsiny\ -\ e^x.ycosy)dx\ +\ (e^x.cosy\ +\ xe^xcosy\ -\ ye^xsiny)dy[/tex]
on integrating both side, we get
[tex]\int{dv}\ =\ \int{e^x.xsiny\ +\ e^xsiny\ +\ e^x.ycosy)dx}\ +\ \int{(e^x.cosy\ +\ xe^xcosy\ -\ ye^xsiny)dy}[/tex]
[tex]=>\ v\ =\ 2xe^xsiny\ +\ 2ye^xcosy\ +\ c[/tex]
[tex]=\ 2e^x(xsiny\ +\ ycosy)\ +\ c[/tex]
hence, the conjugate equation can be given by
[tex]v\ =\ 2e^x(xsiny\ +\ ycosy)\ +\ c[/tex]